2013
DOI: 10.11622/smedj.2013195
|View full text |Cite
|
Sign up to set email alerts
|

Painful pretibial pseudocyst at bioabsorbable interference screw aperture two years after anterior cruciate ligament reconstruction

Abstract: We report the case of a patient with a painful subcutaneous nodule, measuring 13 mm × 17 mm, at the pretibial graft aperture site, which presented two years after a successful anterior cruciate ligament reconstruction with an autologous hamstring graft. A bioabsorbable poly-L-lactide interference screw was used for graft fixation at the tibial aperture. The patient underwent surgical excision of the lesion and curettage at the tunnel aperture. Grossly, extruded fragments of the screw and a thick pseudocapsule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The publication dates of the included studies ranged from 1999 to 2019. Using the adjusted Oxford Center For Evidence‐Based Medicine criteria [74, 75] for the level of evidence we found that 1 study was Level I [11], 1 Level II [25], 1 Level III [57] and 34 studies were level IV [1, 3, 10, 12–17, 19–21, 23, 29, 33, 36, 42, 43, 46, 49, 51, 53, 54, 56, 58, 59, 62, 64–66, 69, 71, 72] case series or case reports.…”
Section: Resultsmentioning
confidence: 99%
“…The publication dates of the included studies ranged from 1999 to 2019. Using the adjusted Oxford Center For Evidence‐Based Medicine criteria [74, 75] for the level of evidence we found that 1 study was Level I [11], 1 Level II [25], 1 Level III [57] and 34 studies were level IV [1, 3, 10, 12–17, 19–21, 23, 29, 33, 36, 42, 43, 46, 49, 51, 53, 54, 56, 58, 59, 62, 64–66, 69, 71, 72] case series or case reports.…”
Section: Resultsmentioning
confidence: 99%
“…While relatively uncommon, a variety of complications have been noted in case reports after implantation of bioabsorbable screws. Reported complications include bone cysts, 5,9,17,24 pseudocysts, 23 infection, 15,20 extrusion, 1 abscess, 6 and pretibial pain and swelling. 15,22 There have also been 2 case reports of broken screws with associated pathology, either ulceration or chondral lesions.…”
Section: Discussionmentioning
confidence: 99%
“…We also recorded any cyst formation, as this has been noted to be a complication of bioabsorbable screws in previous studies. 5,9,17,23,24…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Further, cases of painful pretibial cysts have been reported. 5 Such cysts typically are diagnosed by MRI scans, and the cyst and screw remnants are traditionally removed by open extirpation. 3 We report on the use of ultrasound (US) examination for diagnosing painful late tibial cyst formation, the precise perioperative localization of screw remnants by US, and the endoscopic removal of the screw remnants along with the surrounding cyst (by ordinary arthroscopic equipment).…”
mentioning
confidence: 99%